Saberes previos del contenido textual y la comprensión de textos expositivos en alumnos del 5° grado de primaria - Ato Burqui, Tempora (2010)
This descriptive research is aimed at demonstrate the relationship between knowledge Prior reports on the textual content and understanding expository texts in the 5th grade students of education primary school in a state of Callao. The sample consisted of 147 students. To measure reading comprehension using battery Assessment of Reading Processes (PROLEC-SE, Cuetos, 2000) and prior knowledge was used Evaluation test of prior knowledge (Ato, 2010). The design was correlational and to establish the degree of association between variables was used Spearman’s rho statistic. The results show that there is statistically significant at 0.01 levels between the variables prior knowledge of textual content and comprehension of expository texts.